2019
DOI: 10.1088/1361-648x/ab09b8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum transport through the edge states of zigzag phosphorene nanoribbons in presence of a single point defect: analytic Green’s function method

Abstract: Zigzag phosphorene nanoribbons have quasi-flat band edge modes entirely detached from the bulk states. We analytically study the electronic transport through such edge states in the presence of a localized defect for semi-infinite and finite ribbons. Using the tight-binding model, we derive analytical expressions for the Green's function and transmission amplitude of both pristine and defective nanoribbons. We find that the transmission of both semi-infinite and finite ribbons is sensitive to the location of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…While it is sufficient 35,36 to describe the low-energy region of the band structure of phosphorene by considering the hopping integrals up to the fifth-nearest neighbors (see Fig. 1 (b)), we only keep the important hopping terms to the first-, second-, and fourth-nearest neighbors in our analytic calculations 34,37,38 . The values of these hopping integrals are t 1 = −1.220 eV, t 2 = 3.665 eV, t 3 = −0.205 eV, t 4 = −0.105 eV, and t 5 = −0.055 eV 35 .…”
Section: A Preliminary Conceptsmentioning
confidence: 99%
“…While it is sufficient 35,36 to describe the low-energy region of the band structure of phosphorene by considering the hopping integrals up to the fifth-nearest neighbors (see Fig. 1 (b)), we only keep the important hopping terms to the first-, second-, and fourth-nearest neighbors in our analytic calculations 34,37,38 . The values of these hopping integrals are t 1 = −1.220 eV, t 2 = 3.665 eV, t 3 = −0.205 eV, t 4 = −0.105 eV, and t 5 = −0.055 eV 35 .…”
Section: A Preliminary Conceptsmentioning
confidence: 99%
“…For phosphorene, on the other hand, the previous theoretical studies showed that the edge states emerge at both zigzag and armchair edges [25][26][27][28][29][30][31]. It was also pointed out that the edge states in phosphorene influence the electronic transport [32,33] and performance as a electrocatalyst for the hydrogen evolution reaction [34].…”
Section: Introductionmentioning
confidence: 99%
“…armchair-type carbon nanotubes with site defects [14], armchair graphene nanoconstrictions (GNC) [15], zigzag phosphorene nanoribbons with site defects [16], molecular wires [17,18], graphene nanobubbles [19], graphene heterojunctions [20], graphene nanoribbons with defects [21], and parallel armchair nanotubes [22]. Transparent states have also been analytically demonstrated in atomic chains with impurities following Fibonacci orderings [4], atomic chains with Fano defects [9], and disordered nanotapes with Fano defects [8].…”
Section: Introductionmentioning
confidence: 99%